6 - Leadership in Kenyan Public Universities and the Challenges of Autonomy and Academic Freedom: An Overview of Trends Since Independence - Daniel N. Sifuna (Journal of Higher Education in Africa, 2012)
It is the contention of this article that leadership, governance and manage- ment are key components in addressing the major challenges that face Afri- can universities in general and Kenyan universities in particular. Such chal- lenges range from the function of the university, underfunding, infrastruc- ture, globalisation trends, etc.These issues would be adequately addressed through committed and expert leadership that operates in an environment that guarantees autonomy and academic freedom of the institution, to pro- vide for the delivery of quality service and accountability. However, on the basis of examples from Kenyan public universities,this article demonstrates a complete lack of these key ingredients and, hence, continued poor perfor- mance of the institutions. To address the many challenges being faced by higher education, an innovative organizational and leadership approach is required which taps into the individual and collective stakeholder creative- ness and competencies in pursuit of core university functions. Increased democratisation and participatory decision-making based on mutual gains among the university system components will need to be researched and utilized.